Expression of soluble adenylyl cyclase in acral melanomas. (1st June 2016) - Li, H.; Kim, S. M.; Savkovic, V.; Jin, S. A.; Choi, Y. D.; Yun, S. J.
Summary: Soluble adenylyl cyclase (sAC) regulates melanocytic cells, and is a diagnostic marker for pigmented skin lesions. Because only a few studies on sAC expression in acral melanomas have been performed, we investigated the histopathological significance of sAC expression in 33 cases of acral melanoma, and assessed its diagnostic value in distinguishing melanoma in situ (MIS, n = 17) from acral invasive melanomas ( n = 16) and melanocytic naevi ( n = 11). Acral melanomas exhibited more marked nuclear immunopositivity compared with acral melanocytic naevi. sAC expression significantly correlated with the nuclear morphology of melanocytes and melanoma cells, namely, hyperchromatic nuclei and prominent nucleoli within vesicular nuclei. sAC expression was predominantly observed in the hyperchromatic nuclei of MIS and the prominent nucleoli invasive melanomas, respectively. In vitro culture models of melanocytes and melanoma cell lines exhibited sAC staining patterns similar to those of acral melanomas. Differentiation induction showed that nuclear and nucleolar expression varied depending on cell morphology. sAC immunostaining may be useful for the differential diagnosis of acral melanocytic lesions, and sAC expressed in the nucleus and nucleolus might be related to cytological and nuclear changes associated with invasion and progression of acral melanomas.